Finansijska analiza efekata implementacije CRM na primeru Češke kompanije MEGA A.S. - Harasta, Tomas (Poslovna ekonomija, 2022)
This case study is focused on the analysis of the financial outcomes of the implementation of a CRM system in a Czech company MEGA, a. s. The paper briefly informs about the history of MEGA, a. s. and their process of implementation of the CRM system. Based on this knowledge further analysis of financial indicators have been made. Calculations have been made based on company financial data. The conclusion is based on all quantitative and qualitative data that has been used for the research in this case study. The case study concluded that even though it is very much hard to quantify the outcomes of the implementation of the CRM system, an improvement in various indicators has been observed. That includes for example the productivity per employee or several rentability indicators.